THE IMPACT OF HUMAN CAPITAL ON ECONOMIC GROWTH: THEORETICAL PERSPECTIVES AND EVALUATION APPROACHES (World Economics and Finance Bulletin, 2025)
This research examines the evolution of the concept of human capital, methodological approaches to its assessment, and its relationship with economic growth. Based on indicators such as the Human Development Index, education, health, and digital skills, the study analyzes the dynamics of human capital development in Uzbekistan. The findings confirm that human capital is a key determinant of economic stability and innovative growth. The paper also provides recommendations for improving the national assessment framework.